BAHASA INDONESIA SEBAGAI CERMIN IDENTITAS NASIONAL DI ERA MEDIA SOSIAL - Nadila, Nadila; Eka Dian Safitri; Nonny Rulisty Putri Sutikno (Jurnal Lentera Edukasi, 2025)
This paper discusses the role of the Indonesian language as a symbol of national identity in the rapidly evolving era of social media. The discussion focuses on the shift in language patterns among society, particularly the younger generation, influenced by digital culture. This article is developed through a conceptual approach based on literature review and observations of linguistic phenomena on social media. The study concludes that although there are challenges in preserving the purity of the language, social media can also serve as a positive space to foster appreciation and love for the Indonesian language.